Pingo in the Mackenzie Delta, N.W.T. - Pihlainen, J. A.; Brown, R. J. E.; Legget, R. F. (1956)
Pingoes are conical hills peculiar to arctic regions. Although this note records the results of a study on only one pingo, it is believed that this is the first such detailed investigation in North America. It is hoped that the information will contribute to the understanding of, and stimulate comment on, these arctic phenomena. Peer reviewed: Yes NRC publication: Yes